Recovering a Tradition of Rural Progressivism in American Public Education - David Leo-Nyquist (Journal of Research in Rural Education, 2001)
Dewey-inspired educational progressivism in the first half ofthe 20th century generally has been assumed to have been an urban phenomenon. This article traces a tradition ofrural progressivism during the period J9J0-J950 centered at Teachers College in New York City, and explores the implication ofthat tradition for educators today.